Clinical Case Complexity in Occupational Health: Contributing Factors and a Proposed Conceptual Framework Model. Issue 6 (June 2021) - Lalloo, Drushca; Gallagher, John; Macdonald, Ewan; McDonnell, Conor
Abstract : Objectives: Clinical case complexity is an inherent factor in occupational health (OH), yet it is poorly defined and understood. Our aim was to identify the multiple sources of complexity in OH and propose a conceptual complexity framework model for clinical OH practice. Methods: Through a scoping review, expert panel consensus, and content analysis of OH clinical case reports, we identified relevant complexity-contributing factors (CCFs) specifically tailored to the OH setting, which we defined and validated. Results: The proposed model consists of three primary domains (PDs); health factors, workplace factors and biopsychosocial factors. Twenty-seven CCFs are described and defined within these PDs. Conclusions: This work lays the foundation for improved understanding, identification, and assessment of complexity in OH. This is imperative for ensuring high quality clinical practice standards, identifying training needs and appropriate triaging/resource allocation.